Clinical perspectives, assessment, and mechanisms of metabolic-associated fatty liver disease in patients with COVID-19 - Campos-Murguía, Alejandro; Román-Calleja, Berenice M; González-Regueiro, José A; Hurtado-Díaz-de-León, Ivonne; Solís-Ortega, Alberto Adrián; Flores-García, Nayelli C; García-Juárez, Ignacio; Ruiz-Margáin, Astrid; Macías-Rodríguez, Ricardo Ulises (World journal of gastroenterology : WJG, 2021)
Metabolic diseases are highly prevalent worldwide and have been associated with adverse clinical outcomes, including mortality, in patients developing coronavirus disease (COVID-19). Because of the close relationship between metabolic diseases such as type 2 diabetes mellitus and obesity and the presence of metabolic-associated fatty liver disease (MAFLD), a high number of cases of patients affected by both MAFLD and COVID-19 would be expected, especially in high-risk populations. Some studies have shown an increased risk of adverse clinical outcomes, viral shedding, and deep vein thrombosis, especially in patients with MAFLD- related liver fibrosis. The predisposition to poor outcomes and severe acute respiratory syndrome coronavirus 2 infection in patients with MAFLD could be secondary to mechanisms common to both, including preexisting systemic chronic inflammation, endothelial dysfunction, and involvement of the renin-angiotensin system. Because of the increased risk of adverse outcomes, MAFLD should be screened in all patients admitted for COVID-19. Available computed tomography scans could be of help, assessment of liver fibrosis is also recommended, favoring noninvasive methods to limit the exposure of healthcare workers. Liver involvement in this population ranges from abnormalities in liver chemistry to hepatic steatosis in postmortem biopsies. Finally, preventive measures should be strongly advocated in patients already known to have MAFLD, including the use of telemedicine and vaccination in addition to general measures.Metabolic diseases are highly prevalent worldwide and have been associated with adverse clinical outcomes, including mortality, in patients developing coronavirus disease (COVID-19). Because of the close relationship between metabolic diseases such as type 2 diabetes mellitus and obesity and the presence of metabolic-associated fatty liver disease (MAFLD), a high number of cases of patients affected by both MAFLD and COVID-19 would be expected, especially in high-risk populations. Some studies have shown an increased risk of adverse clinical outcomes, viral shedding, and deep vein thrombosis, especially in patients with MAFLD- related liver fibrosis. The predisposition to poor outcomes and severe acute respiratory syndrome coronavirus 2 infection in patients with MAFLD could be secondary to mechanisms common to both, including preexisting systemic chronic inflammation, endothelial dysfunction, and involvement of the renin-angiotensin system. Because of the increased risk of adverse outcomes, MAFLD should be screened in all patients admitted for COVID-19. Available computed tomography scans could be of help, assessment of liver fibrosis is also recommended, favoring noninvasive methods to limit the exposure of healthcare workers. Liver involvement in this population ranges from abnormalities in liver chemistry to hepatic steatosis in postmortem biopsies. Finally, preventive measures should be strongly advocated in patients already known to have MAFLD, including the use of telemedicine and vaccination in addition to general measures.